2021
DOI: 10.1161/circep.120.009261
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Feasibility of Left Bundle Branch Pacing in a Large Single-Center Study

Abstract: Background - Left bundle branch pacing (LBBP) is a novel pacing method and has been observed to have low and stable pacing thresholds in prior small short-term studies. The objective of this study was to evaluate the feasibility and safety of LBBP in a large consecutive diverse group of patients with long-term follow up. Methods - This study prospectively enrolled 632 consecutive pacemaker patients with attempted LBBP from April 2017 to July 2019. Pacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
255
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(319 citation statements)
references
References 33 publications
21
255
3
2
Order By: Relevance
“…After LBBP upgrade, 10 patients developed a normal QRS transition and nine patients demonstrated an R/S transition between leads V1 and V2. In our study, a normal QRS axis was maintained with LBBP in most cases and reversed PICM as we previously reported ( 14 ). LBBP deliberately targeted the more proximal left bundle in our study, while some LBBP case reports showed left axis deviation for pacing sites located near the left posterior branch ( 14 , 23 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…After LBBP upgrade, 10 patients developed a normal QRS transition and nine patients demonstrated an R/S transition between leads V1 and V2. In our study, a normal QRS axis was maintained with LBBP in most cases and reversed PICM as we previously reported ( 14 ). LBBP deliberately targeted the more proximal left bundle in our study, while some LBBP case reports showed left axis deviation for pacing sites located near the left posterior branch ( 14 , 23 ).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, no patients had lead dislodgment, perforation, or threshold increase during a median 12-month follow-up as indicated (14,30). LBBP is deep enough to penetrate the septum with capture of both the left bundle and the left ventricular septum (22).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The lead was screwed deeply into the interventricular septum until the paced QRS complex changed from an LBBB to a RBBB morphology. LBB capture was confirmed using RBBB paced morphology and one of the following signs: (1) selective LBBP (SLBBP) (paced morphology as a typical RBBB shape with a discrete component in intracardiac electrogram); (2) stimulus to left ventricular activation time (Sti-LVAT) shortening abruptly by >10 ms with increasing output or remaining shortest and constant at the final site (2,(12)(13)(14). When LBB capture threshold was lower than the local myocardium capture threshold, SLBBP could be achieved at low output while nonselective LBBP (NSLBBP) at high output ( Figures 1A,B).…”
Section: Implantation Procedures Of Lbbpmentioning
confidence: 99%
“…Although HBP may be more effective to achieve ventricular activation to the physiological level than LBBAP, pilot studies have showed a few technical advantages of LBBAP over HBP, including lower and more stable thresholds, higher implant success rates, and comparable ventricular mechanical synchrony of similar magnitude as HBP ( 13 ). With the accumulated experiences and continuous advances in implantation techniques, LBBAP may become an alternative strategy to HBP for CRT delivering with conduction system pacing ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%